Faktor-Faktor Yang Mempengaruhi Pendapatan Rumah Tangga Migran Nonpermanen di Kecamatan Denpasar Selatan - Naning Suciati, Ayu; Marhaeni, A.A I.N (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 6, Juni 2019, pp (1181-1442), 2019)
Mobility is reflection of the differences in economic welfare and the lack integration of development facilities among regions. Welfare differences between one area and another can be driving factor for migration. Theqpurposeoofstheastudysis to determine the influence of education, the number of dependents and working hours to income nonpermanent migrant house hold in south Denpasar. 74 sample were taken with nonprobability sampling method. Thesresultoof multiple linear regression analysis showed the variables of education, number of dependents and working hours simultaneously and partially had a significant effect on the income of nonpermanent migrant house hold in south Denpasar. Educational variables are dominant influential variables.This shows level of education has a positive role increasing income of nonpermanent migrant house hold in south Denpasar. Keyword: migrant, education, number of dependents, working hours, income